In what way can banks support the transition to a sustainable economy? - Kulińska-Sadłocha, Ewa (W poszukiwaniu zielonego ładu, 2022)
The aim of this chapter is to asses opportunities and methods that banks can use to influence the transition towards a sustainable economic model. Due to the specificities of their duties, banks are institutions with substantial influence over their environment, including effective shift in the structure of financing from activities that cause harm to the natural environment and society towards activities that are in line with the concept of sustainable development. Banks can do so by integrating Environmental, Social, and Governance (ESG) risk into risk management, as well as by offering a range of sustainable financial services and products.